Sustainabilitas alami Lontar ( Borassus flabellifer L.) di desa Linamnutu, Timor Tengah Selatan, Nusa Tenggara Timur - Sancayaningsih, Retno Peni; Santosa, Sigit Heru Murti Budi; Utami, Asri Vidya (2014)

(untitled)
Sustainabilitas alami Lontar (Borassus flabellifer L.) di desa Linamnutu, Timor Tengah Selatan, Nusa Tenggara Timur